Registro eletrônico de saúde: desafios da implantação - Mauer, Thais Ciarallo [UNIFESP] (2017)
The initial contributions of computer science for the health area intensified the studies, researches and investments in the development of the technology resources used for the healthcare advancement. The acknowledged field from these actions, called Health Informatics simultaneously succeeded, getting effective results while it faced several obstacles, such as the challenges of implementation and assessment of Health Information Systems. Although the Electronic Health Record (EHR) is recognized as a powerful trend and that considerable advantages in relation to the paper record have been proved, there are still many obstacles regarding its implementation. This study aimed to investigate the implementation process of the Electronic Health Record. The methodology has been developed in four stages, as follows: translation of the assessment tool “Clinical Information System Implementation Evaluation Scale (Cisies)”; validation of the assessment tool translation; categorizing of the assessment tool sentences “Effectiveness Scale of the Clinical Information Systems Implementation”; assessment tool test. As a result of the questionnaires application, according to the Cisies score scale, the average score of all the items for the ambulatory collected data was 1,91, while in hospital was 0,97. Both results fit in the same interpretative category. However, scores ranging from 1,5 to 1,99 might also be an indicative of appropriate to moderate satisfaction. On the other hand, scores ranging from 0,5 to 1,99 suggest that at least an error with the system implementation has occurred. Through the collected and researched results, it’s been concluded that there’s no specific formula that could guarantee success in the EHR implementation. It’s been pointed that it is the result of a thorough project planning, scheduling, responsible team nomination with their corresponding role duties, well-elaborated plans for dealing with eventualities and unforeseen circumstances. The literature points to the necessity of engagement of several actors in the EHR adoption process, such as: information technology professionals, assistance, healthcare managers, general users, researchers, Health Information Systems experts, software industries, governmental agencies and patients. Related experiments in other institutions that had already been through the EHR implementation process may be key elements for contributing in the system adoption planning. Thus, although there are many obstacles among the EHR proposals and the effective success in its implementation, many are the “best xiv practices” that can be used to achieve it. And, it’s worth to highlight that the key factor for the success might be the acknowledgement that the main goal in the EHR utilization is the improvement of patients’ healthcare.